Investigating the effect of three nitrate fertilizers on nitrate leaching under the root zone in clay loam soil - Mohammed, Thamer Ahmed; Mostofi, Nooshin; Megat Mohd Noor, Megat Johari; Liaghat, Abdolmajid (Science Publications, 2009)
Problem statements: Nitrogen fertilizer is recognized as an important factor in crop’s yield level, however more application of N fertilizers in the soil have some adverse effects on environment and especially on groundwater contamination. Perception and recognition the factors influencing nitrate transport through soil profile is helpful for fertilizer management to minimize adverse impacts on environment and nitrate leaching below the root zone. Approach: In this study, 9 large cylindrical lysimeters with 1 m height and 0.5 m diameter were filled with clay loam soil and planted with maize to investigate nitrate leaching under different types of N-fertilizer, chemical fertilizer, activated sludge and organic manure. Nitrate concentration in the soil and drainage water samples were analyzed by spectrophotometer method and the mass of nitrate was calculated in soil and drainage water. Crop productions for different treatments were compared too. Results: Results showed that cumulative mass of nitrate leaching from organic fertilizer was greater than the other treatments (229 kg ha-1). Organic manure had the greatest nitrate accumulation in soil (15.17 mg kg-1), which was significantly greater than chemical fertilizer. Conclusions/Recommendations: Experimental results showed that manure application could result in NO3--N accumulation increase in the deeper soil profiles compared with activated sludge. Results showed that maize production was significantly higher under activated sludge fertilizer. Observations made in the current study suggest activated sludge fertilizer due to a higher crop production with same level of groundwater contamination, especially in clay loam soils.